Fruit vinegars attenuate cardiac injury via anti-inflammatory and anti-adiposity actions in high-fat diet-induced obese rats - Abdenour Bounihi; Arezki Bitam; Asma Bouazza; Lyece Yargui; Elhadj Ahmed Koceir (Taylor & Francis Group, 2017)
Context: Fruit vinegars (FVs) are used in Mediterranean folk medicine for their hypolipidemic and weight-reducing properties. Objective: To investigate the preventive effects of three types of FV, commonly available in Algeria, namely prickly pear [Opuntia ficus-indica (L.) Mill (Cectaceae)], pomegranate [Punica granatum L. (Punicaceae)], and apple [Malus domestica Borkh. (Rosaceae)], against obesity-induced cardiomyopathy and its underlying mechanisms. Materials and methods: Seventy-two male Wistar rats were equally divided into 12 groups. The first group served as normal control (distilled water, 7 mL/kg bw), and the remaining groups were respectively treated with distilled water (7 mL/kg bw), acetic acid (0.5% w/v, 7 mL/kg bw) and vinegars of pomegranate, apple or prickly pear (at doses of 3.5, 7 and 14 mL/kg bw, acetic acid content as mentioned above) along with a high-fat diet (HFD). The effects of the oral administration of FV for 18 weeks on the body and visceral adipose tissue (VAT) weights, plasma inflammatory and cardiac enzymes biomarkers, and in heart tissue were evaluated. Results: Vinegars treatments significantly (p < .05) attenuated the HFD-induced increase in bw (0.2-0.5-fold) and VAT mass (0.7-1.8-fold), as well as increase in plasma levels of CRP (0.1-0.3-fold), fibrinogen (0.2-0.3-fold), leptin (1.7-3.7-fold), TNF-α (0.1-0.6-fold), AST (0.9-1.4-fold), CK-MB (0.3-1.4-fold) and LDH (2.7-6.7-fold). Moreover, vinegar treatments preserved myocardial architecture and attenuated cardiac fibrosis. Discussion and conclusion: These findings suggest that pomegranate, apple and prickly pear vinegars may prevent HFD-induced obesity and obesity-related cardiac complications, and that this prevention may result from the potent anti-inflammatory and anti-adiposity properties of these vinegars.